The The Influence Of Good Corporate Governance On Company Performance Reg-istered Transportation On The Indonesia Stock Exchange Period 2020-2023 - Hutabarat, Eloy Charolina; Simanjuntak, Arthur; Sipayung, Tri Dharma (Basic and Applied Accounting Research Journal, 2025)
This study aims to determine the influence of Good Corporate Governance or based on the mechanism of the Audit Committee, Board of Directors, and Board of Independent Commissioners, partially and simultaneously on the Company's Performance in Transportation Companies Listed on the Indonesia Stock Exchange for the 20202-2023 period. The period used in this study is four years, starting from 2020-2023. Samples were taken using the purposive sampling method. The population in this study is all transportation companies that have been and are still listed on the Indonesia Stock Exchange for the 2020-2023 period. From the population of 37 Transportation companies, 11 Transportation companies were obtained as a sample with an observation period of three years (2020-2023). The software analysis used in this study is with IBM SPSS Statistics 26. The results of this study show that the Audit Committee variables have no direct effect and are not significant on the company's performance. The results of this study also show that the variables of the Board of Directors that directly have a significant influence on the company's performance. The Board of Independent Commissioners has an influence and significance on the Company's Performance. And the Audit Committee, Board of Directors and Board of Independent Commissioners simultaneously affect the Performance of Transportation Companies listed on the Indonesia Stock Exchange for the 2020-2023 period.